Coupling spin defects in hexagonal boron nitride to titanium dioxide ring resonators. Issue 40 (7th September 2022) - Nonahal, Milad; Li, Chi; Tjiptoharsono, Febiana; Ding, Lu; Stewart, Connor; Scott, John; Toth, Milos; Ha, Son Tung; Kianinia, Mehran; Aharonovich, Igor
Abstract : Spin defects in hexagonal boron nitride are coupled to microring cavity resonator. Abstract : Spin-dependent optical transitions are attractive for a plethora of applications in quantum technologies. Here we report on utilization of high quality ring resonators fabricated from TiO2 to enhance the emission from negatively charged boron vacancies (VB − ) in hexagonal Boron Nitride. We show that the emission from these defects can efficiently couple into the whispering gallery modes of the ring resonators. Optically coupled VB − showed photoluminescence contrast in optically detected magnetic resonance signals from the hybrid coupled devices. Our results demonstrate a practical method for integration of spin defects in 2D materials with dielectric resonators which is a promising platform for quantum technologies.